Investigation of the photochemical, sono-photochemical and biological characteristics of novel zinc and indium Schiff base phthalocyanines - Celep, Kevser; Atmaca, Goknur Yasa; Aydogmus, Pelin Demir; Eroglu, Kumsal; Gunkara, Omer Tahir; Dundar, Abdurrahman; Yalcin, M. Serkan; Ozdemir, Sadin; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study focuses on synthesizing novel Schiff-base substituted zinc and indium phthalocyanines (Pcs) to utilize the sono-photochemical approach to enhance therapeutic efficacy in cancer treatment. The research specifically investigates sensitizers through photochemical and sono-photochemical methods with the primary goal of producing singlet oxygen. In this study, the complexes showed high singlet oxygen quantum yields, (Phi Delta PDT) = 0.62, (Phi Delta SPDT) = 0.81 for P3 (ZnPc) and (Phi Delta PDT) = 0.74, (Phi Delta SPDT) = 0.93 for P4 (InPc). The findings demonstrate that sono-photochemical properties enhance singlet oxygen generation more effectively than photochemical properties alone. This study also investigates the biological properties of the synthesized phthalocyanines to evaluate a variety of potential drug-related applications. In this context, it was observed that P4 and P3 showed 79.39 % and 48.79 % antioxidant ability at 100 mg/L concentration in DPPH free radical scavenging activity, and both molecules showed 100 % antidiabetic activity at 100 mg/mL concentration. The inhibition activity of P4 against the biofilm produced by S. aureus and P. aeruginosa at the 15 mg/L concentration was 87.99 % and 84.61 %, respectively, while the same order for P3 was 74.51 % and 69.83 %, respectively. Light exposure increased the toxicity of both molecules against E. coli. At a concentration of 15 mg/L, P4's E. coli inhibition was 99.11 %, meanwhile P3's E. coli inhibition was found as 92.58 %. While P3 and P4 molecules created double-strand strand breaks in the pBR 322 DNA at 50 and 100 mg/L, they fragmented the DNA completely at 200 mg/L. Antimicrobial activity of samples evaluated by minimum inhibitory concentration (MIC) values. The powerful antimicrobial activity exhibited by P4 against L. pneumophila as 8 mg/L when the weakest activity was shown by P3 against C. parapisiolis and C. tropicalis as 64 mg/L.
Keywords: DNA cleavage; Cell viability; Sono-photochemical; Biofilm prevention; Antibacterial effects; PHOTODYNAMIC THERAPY; Chemistry; Crystallography